The Appraisal Approach to Aging and Emotion: An Integrative Theoretical Framework - Young, Nathaniel A. (Dev Rev, 2021)
To advance our understanding of how emotional experience changes across the adult life span, we propose an integrative theoretical framework: the appraisal approach to aging and emotion (AAAE). AAAE posits that (a) age-related cognitive, motivational, and physical changes fundamentally change the appraisal system in certain ways, and that (b) older adults often deploy appraisal processes in different ways relative to their younger counterparts. As such, we hypothesize that these age-related changes to the appraisal process underlie the finding that older and younger adults tend to experience different emotions. In this paper we integrate findings from the aging literature with appraisal theory, grounding AAAE in theoretical and empirical work relevant to the relationship between aging and appraisal processes. Using our theoretical framework, it is possible to identify critical points of investigation for aging and emotion researchers to further develop our understanding of the proximal-level determinants of age differences in emotion.